Czech Art 1900-1990 : from the collection at the Prague City Gallery - House of the Golden Ring. - Bydzovska, Lenka; Fatka, Jaroslav; Halirova, Marie; Lahoda, Vojtech; Petricek, Miroslav Jr.; Srp, Karel (Praha : Prague City Gallery)
Balcar, Jiri ; Bauch, Jan ; Bilek, Alois ; Bilek, Frantisek ; Bostik, Vaclav ; Boudnik, Vladimir ; Cisarovsky, Tomas ; David, Jiri ; Demartini, Hugo ; Divis, Alén ; Divis, Stanislav ; Drtikol, Frantisek ; Feuerstein, Bedrich ; Filla, Emil ; Gross, Frantisek ; Gutfreund, Otto ; Hejna, Vaclav ; Horejc, Jaroslav ; Hudecek, Antonin ; Hudecek, Frantisek ; Chad, Vaclav ; Janousek, Frantisek ; Janousek, Vladimir ; Janouskova, Vera ; Jetelova, Magdalena ; Kmentova, Eva ; Kofránek, Ladislav Jan ; Kokolia, Vladimir ; Kolar, Jiri ; Kolibal, Stanislav ; Kopecky, Vladimir ; Kotik, Pravoslav ; Kratina, Radoslav ; Kremlicka, Rudolf ; Kucerova, Alena ; Landa, Antonin ; Lhotak, Kamil ; Mainer, Martin ; Malich, Karel ; Medek, Mikulas ; Merta, Jan ; Muzika, Frantisek ; Naceradsky, Jiri ; Nejedly, Otakar ; Nemec, Rudolf ; Nepras, Karel ; Palcr, Zdenek ; Panuska, Jaroslav ; Pesanek, Zdenek ; Piesen, Robert ; Ponc, Miroslav ; Prucha, Jindrich ; Rittstein, Michael ; Róna, Jaroslav ; Ságner, Augustin ; Sekal, Zbysek ; Slavicek, Antonin ; Slavik, Otakar ; Smetana, Jan ; Sopko, Jiri ; Stavinoha, Eduard ; Stefan, Bedrich ; Strizek, Antonin ; Svobodová, Jitka ; Sýkora, Zdenek ; Sima, Josef ; Simon, Tavik Frantisek ; Stursa, Jan ; Styrsky, Jindrich ; Svabinsky, Max ; Teige, Karel ; Tichy, Frantisek ; Tomalik, Antonin ; Toyen ; Váchal, Josef ; Válová, Jitka ; Válová, Kvéta ; Vesely, Ales ; Zippe, Stanislav ; Zivr, Ladislav ; Zrzavý, Jan ; Zykmund, Václav
Exhibitions organised exclusively from the art collections at the Prague City Gallery p. 237-239, List of exhibits p. 263-278, bibliog. p. 243-262
Engels
boek
Keywords: Tsjechië